Designing pharmacogenomic studies to be fit for purpose. (December 2010) - Burns, Daniel K; Hughes, Arlene R; Power, Aidan; Wang, Sue-Jane; Patterson, Scott D
The 2010 US FDA–Drug Industry Association (DIA) Pharmacogenomics Workshop, the fifth in a series of meetings that begun in 2002, brought together multidisciplinary experts from regulatory authorities, medical research, healthcare and drug development. This article summarizes the 'Designing Pharmacogenomic Studies to be Fit for Purpose' track in which considerations regarding the use of retrospective and prospective studies were examined in relation to their ability to influence treatment decisions and labeling for drugs. The aim of the session, using real-world examples ( KRAS /panitumumab and HLA-B*5701 /abacavir), was to identify good scientific principles that would guide the design of studies to identify subgroups of responders during development programs (including marketed drugs), which could subsequently be used to guide treatment decisions.